Motivation and Performance of Primary School Teachers’ in Uganda: Acase Study of Kayonza Primary Schools in Kanungu District. - Atukunda, Bright (Kabale University, 2024)
The study examined the motivation and performance of primary school teachers in Uganda, focusing on Kayonza Primary Schools in Kanungu District. Its objectives were to identify the factors that influence teacher motivation in the district, evaluate the impact of motivation on teacher performance, and explore the relationship between intrinsic and extrinsic motivation and teacher performance. A descriptive research design was utilized, with data collected through interviews and questionnaires. Regarding factors influencing motivation, the majority of respondents indicated that teachers are mainly motivated by salaries and wages, while fewer respondents mentioned that hard-to-reach allowances also contribute to motivation. Concerning the impact of motivation on performance, most respondents stated that motivated teachers work confidently, love their job, and inspire students to work hard and perform well. A smaller group of respondents highlighted that motivation attracts competent teachers, leading to better quality work and improved student performance. The study also revealed a strong positive correlation between intrinsic and extrinsic motivation and teacher performance. It recommended that management should ensure employees understand the organization’s strategies and processes, engage in discussions with staff, and consider their feedback on how they wish to be treated.